Effect of Variation H2SO4 on the Manufacture of Nanocellulose from Corn Cobs - Pertiwi, Mega; Manurung, Posman; Suciyati, Sri Wahyu; Karo, Pulung Karo (Journal of Energy, Material, and Instrumentation Technology, 2024)
The acid hydrolysis method has been used to manufacture nanocellulose from corn cobs. This study aims to determine the effect of variations in the concentration of H2SO4 on the characteristics of nanocellulose produced from corn cobs and their surface morphology. The variations of H2SO4 used were 5, 10, 15, and 20%. X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) are characterizations used. The results of XRD characterization showed that the crystallite size obtained followed the nanocellulose crystallite size, which was 1.79-2.59 nm. The SEM characterization showed that the resulting nanocellulose’s surface morphology was lumpy and non-porous.